Analytic Assessment On Students’ Ability In Writing Descriptive Text - Sumartono Sumartono (Cakrawala: Jurnal Pendidikan, 2019)
This study is aimed at describing students’ ability in writing descriptive texts viewed from analytic assessment presented by O’Malley and Pierce, involving composing, style, sentence formation, usage and mechanics. The study was conducted by applying a descriptive quantitative-qualitative method. The data were taken from 15 descriptive texts made by the second semester students of English Department, Pancasakti University Tegal 2018/2019. The result of the study shows that there are 33.4% of the students are “good”, 40% of the students are “fair”, and 26.6% of the students are “bad”. The students mean score is 65 (fair), and the scores of each components are as follows: composing is 71.6, style is 66.2, sentence formation is 60, usage is 55.7, and mechanics is 55. The result also shows that the texts are developed trough correct generic structure involving identification and descriptions. The writer suggested that the students need to study harder and practice more frequently to increase their writing ability, specifically in mechanics as their weakness in writing.